Manufacturing method for lithium ion conduction sheet
Patent Information
- Application Number
- JP2023138664
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-03-13
AI Technical Summary
【0007】 本発明の一側面によれば、大型化しても耐久性に優れたリチウムイオン伝導シートの製造方法を提供することができる。
Smart Images

Figure 2025033148000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a lithium ion conductive sheet. [Background technology]
[0002] In order to recover lithium from liquids such as seawater, the use of a sheet capable of conducting lithium ions has been considered. For example, Patent Document 1 discloses a method for producing a lithium separation sheet, which includes a step of firing a molded product. Patent Document 1 describes forming a molded product by coating a mixture containing raw materials. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2021-160945 Summary of the Invention [Problem to be solved by the invention]
[0004] From the viewpoint of improving the efficiency of lithium recovery, the enlargement of the lithium ion conductive sheet as described above is being considered. However, simply increasing the size of the lithium ion conductive sheet tends to make the sheet more susceptible to damage.
[0005] Therefore, an object of one aspect of the present invention is to provide a method for producing a lithium ion conductive sheet that has excellent durability even when made large. [Means for solving the problem]
[0006] In view of the above circumstances, the present inventors conducted extensive research and completed the inventions described below in [1] to [5]. [1] A first step of forming a plurality of green sheets by drying a coating of a slurry containing a lithium raw material, a lanthanum raw material, and a titanium raw material; a second step of laminating a plurality of green sheets together to form a laminate; A third step of pressing the laminate; A fourth step of firing the pressed laminate. [2] The slurry further comprises a binder, a plasticizer, a dispersant, and a solvent; The content of the binder is 10.0% by mass or more and 40.0% by mass or less based on the total amount of solids in the slurry, The content of the plasticizer is 1.0% by mass or more and 20.0% by mass or less based on the total amount of solids in the slurry, The method for producing a lithium ion conductive sheet according to [1], wherein the content of the dispersant is 1.0 mass % or more and 5.0 mass % or less based on the total amount of solids in the slurry. [3] The method for producing a lithium ion conductive sheet according to [1] or [2], wherein in the third step, the laminate is pressed at a pressure of 130 kPa or more and 1,380 kPa or less under conditions of 30°C or more and 200°C or less to bond the laminate. [4] The method for producing a lithium ion conductive sheet according to any one of [1] to [3], wherein in the second step, an organic solvent is applied to a surface of at least one of the plurality of green sheets, and then the plurality of green sheets are laminated together. [5] The method for producing a lithium ion conductive sheet according to any one of [1] to [4], wherein interfaces between multiple green sheets present on the side surfaces of the laminate in the second step disappear by the end of the third step. Effect of the Invention
[0007] According to one aspect of the present invention, there is provided a method for producing a lithium ion conductive sheet that has excellent durability even when made large. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a lithium ion conductive sheet. [Diagram 2]FIG. 2 is a schematic diagram of an example of a lithium recovery device using a lithium ion conductive sheet. [Diagram 3] 3(a), (b), and (c) are diagrams illustrating a method for producing a lithium ion conductive sheet according to an embodiment. [Figure 4] FIG. 4 is an image of the main surface of the lithium ion conductive sheet produced in Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment according to one aspect of the present invention will be described in detail with reference to the drawings. In the description of the drawings, the same or equivalent elements are designated by the same reference numerals, and duplicated description will be omitted.
[0010] <Lithium ion conductive sheet> An example of a lithium ion conductive sheet manufactured by the manufacturing method according to an embodiment is: Contains lithium lanthanum titanate, The area of the main surface is 26 cm 2 More than 400cm 2 is as follows: The thickness is 800 μm or more and 2000 μm or less, The lithium ion conductive sheet has a thickness variation coefficient of 0.045 or less.
[0011] The lithium ion conductive sheet has a main surface area of 26 cm 2 More than 400cm 2 Since the thickness of the lithium ion conductive sheet is large, at 800 μm or more and 2000 μm or less, and the coefficient of variation of the thickness is 0.045 or less, the sheet has excellent durability.
[0012] The lithium ion conductive sheet will now be described in detail.
[0013] FIG. 1 is a schematic cross-sectional view showing an example of a lithium ion conductive sheet. The lithium ion conductive sheet 1 shown in FIG. 1 is an inorganic sheet used for recovering lithium from, for example, seawater, salt lake brine, and a dissolving solution of a discarded LIB (lithium ion battery). The lithium ion conductive sheet 1 exhibits a function of selectively transmitting (conducting) lithium ions contained in a liquid. The lithium ion conductive sheet 1 can also be used as a solid electrolyte. When viewed in the thickness direction of the sheet, the lithium ion conductive sheet 1 has, for example, a rectangular shape, but is not limited thereto. In the following, viewing in the thickness direction of the sheet corresponds to a planar view.
[0014] The lithium ion conductive sheet 1 has a thickness of 800 μm or more and 2000 μm or less. Since the lithium ion conductive sheet 1 has a thickness of 800 μm or more, the lithium ion conductive sheet 1 has excellent durability and is not easily broken. Since the lithium ion conductive sheet 1 has a thickness of 2000 μm or less, the lithium ion conductive sheet 1 has excellent thickness uniformity. From the viewpoint of making the lithium ion conductive sheet 1 more difficult to break, the lithium ion conductive sheet 1 may have a thickness of 850 μm or more, 900 μm or more, 950 μm or more, or 1000 μm or more. From the viewpoint of lithium ion conductivity, the lithium ion conductive sheet 1 may have a thickness of 1500 μm or less.
[0015] The thickness of the lithium ion conductive sheet 1 means the arithmetic average of thicknesses at any nine points on the lithium ion conductive sheet 1. More specifically, it can be determined by the method described in the examples.
[0016] The coefficient of variation of the thickness of the lithium ion conductive sheet 1 is 0.045 or less. Therefore, the lithium ion conductive sheet 1 is not easily broken even though it is large (i.e., has excellent durability). From the viewpoint of making the lithium ion conductive sheet 1 more difficult to break, the coefficient of variation may be 0.040 or less, 0.035 or less, 0.030 or less, or 0.026 or less. The coefficient of variation may be 0.001 or more.
[0017] The coefficient of variation of the thickness of the lithium ion conductive sheet 1 means a value calculated by measuring the thickness at any 9 points on the lithium ion conductive sheet 1 and calculating the following formula based on the arithmetic mean and standard deviation of the obtained data. More specifically, it can be calculated by the method described in the Examples. "Thickness variation coefficient" = standard deviation / arithmetic mean
[0018] The lithium ion conductive sheet 1 has a first main surface 1a and a second main surface 1b. The first main surface 1a and the second main surface 1b are surfaces located on opposite sides of the lithium ion conductive sheet 1 in the thickness direction, and have, for example, a rectangular or circular shape. In order to efficiently transmit lithium ions, a Li adsorption film or the like that adsorbs lithium ions may be formed on at least one of the first main surface 1a and the second main surface 1b. The Li adsorption film is a surface treatment film in which some of the elements contained in the lithium ion conductive sheet 1 are replaced with hydrogen.
[0019] The area of each of the first main surface 1a and the second main surface 1b is 26 cm 2 More than 400cm 2 From the viewpoint of further improving the lithium recovery efficiency, the area is 30 cm 2 More than 50cm 2 More than 70cm 2 Over 90cm 2 or more, or 100cm 2 From the viewpoint of preventing damage to the lithium ion conductive sheet 1, the area of each of the first main surface 1a and the second main surface 1b may be 300 cm or more. 2 Below, 200cm 2 or less than 150cm 2 It may be the following.
[0020] The lithium ion conductive sheet 1 contains lithium lanthanum titanate. The lithium ion conductive sheet 1 is preferably a sintered body containing lithium lanthanum titanate. The lithium lanthanum titanate may be amorphous or crystalline. The lithium lanthanum titanate may be glassy.
[0021] The lithium lanthanum titanate may have a perovskite-type crystal structure. In this case, Li is more likely to move within the lithium ion conductive sheet 1. For example, when the lithium lanthanum titanate has a perovskite-type crystal structure, Li ions in the electrolyte surrounding the lithium ion conductive sheet 1 move through vacancies in the crystal, thereby exerting the Li ion conductivity of the lithium ion conductive sheet 1. At this time, since Li hydrate ions and the like cannot enter the Li site, it is the Li ions (Li + ).
[0022] Lithium lanthanum titanate is an oxide containing at least Li, La, and Ti as constituent elements. Lithium lanthanum titanate may contain only Li, La, Ti, and O as constituent elements. Lithium lanthanum titanate may further contain one or more constituent elements selected from the group consisting of Na, K, Ca, Ba, Si, Pb, Sr, Pr, Nd, Sm, Gd, Dy, Y, Eu, Tb, Ce, Ag, Bi, Mg, Co, Ni, Cu, Cr, Fe, Ga, Gd, In, Sc, Ge, Hf, Mn, Pr, Sn, Tb, Zn, Zr, W, Ru, Nb, Ta, and Al. From the viewpoint of improving the conductivity of lithium ions, lithium lanthanum titanate may contain one or more constituent elements selected from the group consisting of Sr, Ta, and Ba. Lithium lanthanum titanate may be an oxide containing Li, La, Ti, and Sr as constituent elements, or may be an oxide containing Li, La, Ti, Ta, and Ba as constituent elements.
[0023] Lithium lanthanum titanate has the general formula Li 3x La 2 / 3-x-a M 1 a Ti 1-b M 2 b O3, general formula Li 3x-a M 1 a La 2 / 3-x Ti 1-b M 2 b O3, general formula (Li3x La 2 / 3-x ) 1-a M 1 a Ti 1-b M 2 b O3, general formula Li 3x La 2 / 3-x-a M 1 a TiO 3-2a , general formula Li 3x La 2 / 3-x-a M 1 a TiO 3-a , general formula Li 3x La 2 / 3-x Ti 1-b M 2 b O 3―3b , general formula Li 3x La 2 / 3-x Ti 1-b M 2 b O 3―2b , or, general formula Li 3x La 2 / 3-x Ti 1-b M 2 b O 3―b (In each general formula, x, a, and b are numerical values that satisfy 0 < x ≤ 0.3, 0 ≤ a ≤ 0.5, and 0 ≤ b ≤ 0.5, respectively, and M 1 is at least one selected from the group consisting of Na, K, Ca, Ba, Pb, Sr, Pr, Nd, Sm, Gd, Dy, Y, Eu, Tb, Ce, Ag, and Bi, and M 2 is at least one selected from the group consisting of Mg, Co, Ni, Cu, Cr, Fe, Ga, Gd, In, Sc, Ge, Hf, Mn, Pr, Sn, Tb, Zn, Zr, W, Ru, Nb, Ta, Al, and Y.) It may be lithium lanthanum titanate represented by.
[0024] In each of the above general formulas, x may be a numerical value that satisfies 0.05 ≤ x ≤ 0.3, or may be a numerical value that satisfies 0.1 ≤ x ≤ 0.3. In each of the above general formulas, a may be a numerical value that satisfies 0 ≤ a ≤ 0.2. In each of the above general formulas, b may be a numerical value that satisfies 0 ≤ b ≤ 0.2.
[0025] In each of the above general formulas, b may be 0. In this case, lithium lanthanum titanate is represented by the general formula Li 3x La 2 / 3-x-a M 1 a TiO3, general formula Li 3x-a M 1 a La 2 / 3-x TiO3, general formula (Li 3x La 2 / 3-x ) 1-a M 1 a TiO3, general formula Li 3x La 2 / 3-x-a M 1 a TiO 3-2a , general formula Li 3x La 2 / 3-x-a M 1 a TiO 3-a , or the general formula Li 3x La 2 / 3-x Lithium lanthanum titanate is represented by the general formula Li TiO3. In addition, in each of the above general formulas, both a and b may be 0. In this case, lithium lanthanum titanate is represented by the general formula Li 3x La 2 / 3-x It is lithium lanthanum titanate, represented as TiO3.
[0026] The lithium ion conductive sheet 1 may contain compounds other than lithium lanthanum titanate. Examples of other compounds include Li3PO4, LiPO3, Li4SiO4, Li2SiO3, and LiBO2.
[0027] For example, when the lithium ion conductive sheet 1 is manufactured by the manufacturing method described below, the lithium ion conductive sheet 1 may contain voids due to air bubbles. From the viewpoint of lithium ion conductivity, further improvement of durability, etc., the lithium ion conductive sheet 1 may have a ratio of the area of voids when viewed in a direction perpendicular to the main surface to the area of the main surface (hereinafter also referred to as "porosity") of 1% or less. From the same viewpoint, the porosity may be 0.8% or less, 0.5% or less, or 0.3% or less.
[0028] The porosity is calculated by the following formula: Here, the area of the main surface and the area of the void portion in the following formula are determined by photographing the main surface of the lithium ion conductive sheet with a camera from a direction perpendicular to the main surface, and analyzing the obtained photograph with image analysis software (for example, "Image pro plus" manufactured by Hakuto Co., Ltd. System Products Company). Porosity [%] = (area of voids [cm 2 ] / area of main surface [cm 2 ])×100
[0029] FIG. 2 is a schematic diagram of an example of a lithium recovery device using a lithium ion conductive sheet 1. As shown in FIG. 2, an example of a lithium recovery device 100 is similar to the device disclosed in JP 2017-131863 A, and has a treatment tank 101 that accommodates the lithium ion conductive sheet 1, and mesh-shaped electrodes 102 and 103 that sandwich the lithium ion conductive sheet 1. The lithium ion conductive sheet 1 is placed in the treatment tank 101 while being supported by the electrodes 102 and 103, for example. The treatment tank 101 is divided into two regions (a first region 101a and a second region 101b) by the lithium ion conductive sheet 1. The first region 101a is a region that accommodates an electrolyte solution L1 containing lithium ions such as seawater. The second region 101b is a region that accommodates a recovery liquid L2 containing lithium ions extracted from the electrolyte solution L1 by the lithium ion conductive sheet 1. The electrode 102 is a conductive portion accommodated in the first region 101a, and the electrode 103 is a conductive portion accommodated in the second region 101b. The electrodes 102 and 103 are electrically connected to a power source (not shown).
[0030] Next, a method for recovering lithium by the lithium recovery device 100 will be briefly described. First, in the lithium recovery device 100, a voltage is applied to the electrodes 102 and 103 so that the electrode 102 is the positive electrode and the electrode 103 is the negative electrode. As a result, the lithium ions 110 move in the lithium ion conductive sheet 1 toward the electrode 103 functioning as the negative electrode. As a result, the moved lithium ions 110 are selectively accumulated in the recovery liquid L2. Then, lithium can be recovered from the electrolyte solution L1 by extracting the lithium ions 110 (or elemental lithium, lithium compounds, etc.) from the recovery liquid L2. Note that when the electrolyte solution L1 contains metal ions 120 such as sodium ions, these metal ions 120 cannot move in the lithium ion conductive sheet 1. Therefore, even if a voltage is applied to the electrodes 102 and 103, the metal ions 120 remain in the electrolyte solution L1.
[0031] <Method of manufacturing lithium ion conductive sheet> A method for producing a lithium ion conductive sheet according to an embodiment of the present invention includes the steps of: A first step of forming a plurality of green sheets by drying a coating of a slurry containing a lithium raw material, a lanthanum raw material, and a titanium raw material; a second step of laminating the plurality of green sheets together to form a laminate; A third step of pressing the laminate; and a fourth step of firing the compressed laminate.
[0032] In the above manufacturing method, a plurality of green sheets are laminated together in the second step to form a laminate, and then the laminate is compressed in the third step. When one green sheet is thickened by increasing the amount of coating of the slurry, the green sheet tends to have a large thickness variation coefficient, and it takes a long time to dry. In this respect, in the above manufacturing method, a plurality of green sheets are molded in which the thickness variation coefficient is suppressed by not thickening the green sheets, and the plurality of green sheets are laminated. Then, the plurality of green sheets laminated on each other are compressed and integrated to produce a laminated laminate. Therefore, the thickness variation coefficient of the laminated laminate can be reduced. In addition, since the green sheets are not thickened, the time required to dry the green sheets is shorter than that of thickened green sheets. Therefore, according to the above manufacturing method, a lithium ion conductive sheet that is thick but has a small thickness variation coefficient can be produced in a short time.
[0033] Hereinafter, the method for producing a lithium ion conductive sheet according to the present embodiment will be described in detail with reference to Fig. 3. Figs. 3(a), (b), and (c) are diagrams for explaining the method for producing a lithium ion conductive sheet according to the present embodiment.
[0034] (Green sheet molding) First, the green sheet 10 shown in FIG. 3(a) is formed by drying a coating of a slurry containing a lithium (Li) raw material, a lanthanum (La) raw material, and a titanium (Ti) raw material (first step). In one embodiment, in the first step, a slurry containing a lithium raw material, a lanthanum raw material, and a titanium raw material is first generated. Then, the slurry is coated on one side of a substrate film. For example, the slurry is coated by a blade coating method, a doctor blade method, a roll coating method using a die coater or a lip coater, or the like. Then, the coated slurry is dried and peeled off. For example, the slurry is dried under conditions of 100° C. and 2 hours. Before peeling off the dried slurry, the excess part may be removed using a Thomson blade or the like. In this way, the green sheet 10 is formed. By repeating the above operation multiple times, multiple green sheets 10 can be formed. Alternatively, one green sheet may be prepared, and the green sheet may be cut and divided using a Thomson blade or the like to form multiple green sheets 10.
[0035] The green sheet 10 is a plate-like member having a substantially rectangular shape in a plan view. The green sheet 10 has a first main surface 10a and a second main surface 10b. The first main surface 10a and the second main surface 10b are surfaces located on opposite sides of the green sheet 10 in the thickness direction. The first main surface 10a is a contact surface that was in contact with the base film before the green sheet 10 was peeled off from the base film. The first main surface 10a has a surface shape that follows the surface of the base film. The second main surface 10b is an exposed surface that was exposed from the base film before the green sheet 10 was peeled off from the base film. The second main surface 10b may have unevenness due to the raw material powder. The base film is, for example, a resin film such as a polyethylene terephthalate (PET) film. A long green sheet 10 can be formed by using a long base film. The size of the green sheet 10 can be determined, for example, by taking into consideration the size of the fired sheet and the shrinkage rate due to firing.
[0036] The thickness of the green sheet 10 may be 1000 μm or less from the viewpoint of reducing the coefficient of variation of the thickness of the lithium ion conductive sheet 1 to be produced. From the same viewpoint, the thickness of the green sheet 10 may be 900 μm or less, 800 μm or less, or 700 μm or less. From the viewpoint of handleability in the production process, the thickness of the green sheet 10 may be 100 μm or more, 300 μm or more, or 500 μm or more.
[0037] The slurry includes a lithium raw material, a lanthanum raw material, and a titanium raw material. Each raw material is, for example, in a powder form. The slurry is generated, for example, by pulverizing and mixing a powdered lithium raw material, a powdered lanthanum raw material, and a powdered titanium raw material. Hereinafter, the powder including the lithium raw material, the lanthanum raw material, and the titanium raw material is also referred to as raw material powder.
[0038] The lithium raw material is a raw material mainly composed of lithium, such as lithium oxide, lithium carbonate, lithium hydroxide, etc. The lithium raw material may include a single material or multiple materials. The lithium raw material may include only lithium hydroxide, or may include lithium hydroxide and lithium carbonate. The lithium raw material corresponds to a material with the largest lithium content. Therefore, the lithium raw material may include elements other than Li (e.g., Na, K, Ca, Ba, Si, Pb, Sr, Pr, Nd, Sm, Gd, Dy, Y, Eu, Tb, Ce, Ag, Bi, Mg, Co, Ni, Cu, Cr, Fe, Ga, Gd, In, Sc, Ge, Hf, Mn, Pr, Sn, Tb, Zn, Zr, W, Ru, Nb, Ta, Al, etc.). The lithium raw material may include various impurities. For example, even if only lithium carbonate is selected as the lithium raw material, the lithium raw material may include impurities.
[0039] The lanthanum raw material is a raw material mainly composed of lanthanum, such as lanthanum oxide, lanthanum carbonate, lanthanum hydroxide, etc. The lanthanum raw material may include a single material or multiple materials. The lanthanum raw material may include only lanthanum oxide, or may include lanthanum oxide and lanthanum carbonate. The lanthanum raw material corresponds to a material having the largest lanthanum content. Therefore, the lanthanum raw material may include elements other than La, similar to the lithium raw material. The lanthanum raw material may include various impurities. For example, even if only lanthanum oxide is selected as the lanthanum raw material, the lanthanum raw material may include impurities.
[0040] The titanium raw material is a raw material mainly composed of titanium. The titanium raw material is, for example, titanium oxide, titanium hydroxide, various titanates, etc. The titanium raw material may include a single material or may include multiple materials. The titanium raw material may include only titanium oxide, or may include titanium oxide and titanium hydroxide. The titanium raw material corresponds to a material with the largest titanium content. Therefore, the titanium raw material may include elements other than Ti, similar to the lithium raw material and the lanthanum raw material. The titanium raw material may include various impurities. For example, even if only titanium oxide is selected as the titanium raw material, the titanium raw material may include impurities. From the viewpoint of cost reduction, titanium oxide may be used as the titanium raw material. In this case, anatase type titanium oxide (TiO2) may be used, or rutile type titanium oxide (TiO2) may be used.
[0041] In the above slurry, the molar ratio of the lanthanum source to the titanium source (i.e., lanthanum source / titanium source) is, for example, 0.2 or more and 0.65 or less, or 0.2 or more and 0.35 or less, and the molar ratio of the lithium source to the titanium source (i.e., lithium source / titanium source) is, for example, 0.1 or more and 0.5 or less, or 0.1 or more and 0.2 or less.
[0042] The impurities are organic or inorganic substances containing elements other than the above-mentioned main constituent elements (Li, La, and Ti). The impurities are, for example, oxides, chlorides, hydroxides, etc. containing at least one of Na, K, Ca, Ba, Pb, Sr, Pr, Nd, Sm, Gd, Dy, Y, Eu, Tb, Ce, Ag, Bi, Mg, Co, Ni, Cu, Cr, Fe, Ga, Gd, In, Sc, Ge, Hf, Mn, Pr, Sn, Tb, Zn, Zr, W, Ru, Nb, Ta, and Al. The above impurities can be identified and quantified, for example, by ICP analysis, or X-ray diffraction as necessary. These oxides, chlorides, hydroxides, etc. may be intentionally added to the slurry from the viewpoint of improving the lithium ion conductivity of the lithium ion conductive sheet 1 to be manufactured.
[0043] The measured raw materials are mixed by a known method. When the raw materials are in powder form, the raw materials may be pulverized and mixed by using a known mixer / mill. The mixer / mill is, for example, a medium flow type mixer / mill (ball mill, planetary mill, etc.), an agitator type mixer / mill (tower type mill, agitator type mill, flow tube type mill, etc.), or a mortar (agate mortar, alumina mortar, mortar mill, etc.). The raw materials may be mixed in a wet or dry manner. The measured raw materials may be mixed in a mixer such as a container rotary mixer (horizontal cylinder, inclined cylinder, V-type, etc.) or a mechanical agitator mixer (ribbon, screw, rod, etc.), and then the raw materials may be pulverized in a mortar or the like.
[0044] In one embodiment, the weighed lithium raw material, lanthanum raw material, and titanium raw material are wet-mixed in a ball mill to form a slurry without being calcined. In the wet mixing, a solvent is used to disperse each raw material. In addition, after at least a binder is added during the wet mixing, the wet mixing is continued. Thus, in this embodiment, a slurry is formed by wet-mixing the lithium raw material, the lanthanum raw material, the titanium raw material, the binder, and the solvent. As a result, a slurry containing a pulverized mixture of each raw material is formed. For example, a defoaming treatment or the like is performed on the slurry. During the wet mixing, materials different from the raw material powder, the solvent, and the binder may be added. Examples of different materials include a plasticizer, a dispersant, a lubricating aid, a surfactant, an antifoaming agent, and a sintering agent (such as boron). In one embodiment, the slurry may include a binder, a plasticizer, a dispersant, and a solvent in addition to the lithium raw material, the lanthanum raw material, and the titanium raw material.
[0045] In this embodiment, the solvent and the binder are added to the raw material powder in this order, but this is not limited to this. The solvent and the binder may be added to the raw material powder at the same time. The wet mixing is performed, for example, until all the materials contained in the mixture are mixed.
[0046] The binder is appropriately selected from, for example, organic binders and inorganic binders that are well known in the conventional manufacturing methods of ceramic sheets.
[0047] Examples of organic binders include ethylene copolymers, styrene copolymers, acrylate and methacrylate copolymers, vinyl acetate copolymers, maleic acid copolymers, vinyl acetal resins, vinyl formal resins, polyvinyl butyral resins, vinyl alcohol resins, celluloses such as ethyl cellulose, and waxes. Among these, from the standpoint of formability and / or strength of the green sheet 10, and particularly thermal decomposition during mass firing for mass production, alkyl acrylates having an alkyl group with 10 or less carbon atoms, such as methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, isobutyl acrylate, cyclohexyl acrylate, and 2-ethylhexyl acrylate; alkyl methacrylates having an alkyl group with 20 or less carbon atoms, such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, isobutyl methacrylate, cyclohexyl methacrylate, 2-ethylhexyl methacrylate, dodecyl methacrylate, and lauryl methacrylate; Preferred are acrylates; hydroxyalkyl acrylates or hydroxyalkyl methacrylates having a hydroxyalkyl group such as hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, and hydroxypropyl methacrylate; aminoalkyl acrylates or aminoalkyl methacrylates such as dimethylaminoethyl acrylate and dimethylaminoethyl methacrylate; and carboxyl group-containing monomers such as acrylic acid, methacrylic acid, maleic acid, and maleic acid half esters such as monoisopropyl maleate. The number average molecular weight (Mn) of the copolymer or resin contained in the organic binder is preferably 20,000 or more and 200,000 or less, and more preferably 30,000 or more and 100,000 or less. The weight average molecular weight (Mw) of the resin is preferably 100,000 or more and 1,000,000 or less, and more preferably 120,000 or more and 500,000 or less. The dispersity (Mw / Mn) is preferably 1.0 or more and 5.0 or less, and more preferably 1.0 or more and 4.7 or less.The number average molecular weight and the weight average molecular weight are measured, for example, by gel permeation chromatography (GPC). These organic binders can be used alone or in combination of two or more kinds as required. Particularly preferred is a copolymer of monomers containing 60% by mass or more of n-butyl methacrylate and / or 2-ethylhexyl methacrylate.
[0048] As the inorganic binder, for example, at least one selected from zirconia sol, silica sol, alumina sol, titania sol, and the like can be used.
[0049] The content of the binder may be 10.0 mass% or more and 40.0 mass% or less based on the total solid content in the slurry. From the viewpoint of suppressing cracks in the green sheet 10, the content of the binder may be 13.0 mass% or more, 15.0 mass% or more, 17.0 mass% or more, or 20.0 mass% or more based on the total solid content in the slurry, and from the viewpoint of suppressing cracks in the pressed laminate S2 in the fourth step (particularly during degreasing) described later, the content may be 35.0 mass% or less, or 30.0 mass% or less.
[0050] The mass ratio of the raw material powder to the binder in the slurry is not particularly limited. The content of the binder may be 10 parts by mass or more and 80 parts by mass or less, or 20 parts by mass or more and 60 parts by mass or less, relative to 100 parts by mass of the raw material powder. The content of the binder in the slurry is selected according to the performance such as strength and flexibility required for the green sheet 10 and / or the lithium ion conductive sheet after sintering.
[0051] The solvent may be appropriately selected from among solvents known in conventional ceramic sheet manufacturing methods. For example, a solvent appropriately selected from water; alcohols such as ethanol, 2-propanol, 1-butanol, and 1-hexanol; ketones such as acetone and 2-butanone; aliphatic hydrocarbons such as pentane, hexane, and heptane; aromatic hydrocarbons such as benzene, toluene, xylene, and ethylbenzene; and acetates such as methyl acetate, ethyl acetate, and butyl acetate may be used alone or in a suitable mixture of two or more. The amount of the solvent used is adjusted in consideration of the viscosity of the slurry. In this embodiment, a mixed solvent of toluene and ethyl acetate is used as the solvent.
[0052] The plasticizer is added, for example, to impart flexibility to the green sheet 10. Examples of the plasticizer include phthalate esters such as dibutyl phthalate (dibutyl phthalate) and dioctyl phthalate, phthalate polyesters, glycols such as propylene glycol, glycol ethers, and the like.
[0053] The content of the plasticizer may be 1.0% by mass or more and 20.0% by mass or less based on the total solid content in the slurry. The content of the plasticizer may be 2.0% by mass or more, 5.0% by mass or more, 6.0% by mass or more, 7.0% by mass or more, 8.0% by mass or more, 9.0% by mass or more, 10.0% by mass or more, 11.0% by mass or more, or 12.0% by mass or more based on the total solid content in the slurry. When the content of the plasticizer in the slurry is equal to or more than the lower limit, the laminate S1 can be compressed in a shorter time at a lower temperature and under a lower pressure in the third step described later. The content of the plasticizer may be 20.0% by mass or less, 18.0% by mass or less, 15.0% by mass or less, or 13.0% by mass or less based on the total solid content in the slurry, from the viewpoint of suppressing the occurrence of undulation in the laminate S2 compressed in the fourth step described later (particularly during degreasing).
[0054] Dispersants are added, for example, to promote peptization and / or dispersion of the raw material powder. Examples of dispersants include polymer electrolytes such as polyacrylic acid and ammonium polyacrylate, organic acids such as citric acid and tartaric acid, copolymers of isobutylene or styrene and maleic anhydride and their ammonium salts or amine salts, copolymers of butadiene and maleic anhydride and their ammonium salts, etc.
[0055] The content of the dispersant may be 1.0% by mass or more, or 1.5% by mass or more, and 5.0% by mass or less, or 3.0% by mass or less, based on the total amount of solids in the slurry, from the viewpoint of the fluidity of the slurry during coating. The content of the dispersant may be 1.0% by mass or more and 5.0% by mass or less, based on the total amount of solids in the slurry. The above-mentioned "total amount of solids" means the total amount of components forming the green sheet (excluding the solvent that volatilizes during formation). For example, it means the total amount of powder raw materials, binders, plasticizers, dispersants, lubricating aids, surfactants, antifoaming agents, and sintering aids. In addition, when measuring the total amount of solids occupying the slurry, for example, first, about 3 g of the slurry is poured into an aluminum cup, and the weight of the poured slurry (weight before drying) is measured. Next, the solvent contained in the poured slurry is removed by drying it on a hot plate at 110°C for 1 hour in an air atmosphere. Then, the weight of the solid matter remaining on the aluminum cup (weight after drying) is measured and calculated using the following formula. Solid content concentration [%] = (weight after drying [g] / weight before drying [g]) × 100 Total solid content [g] = Slurry weight [g] × Solid content concentration [%] / 100
[0056] (Formation of Laminate) After the first step, as shown in FIG. 3(b), a plurality of green sheets 10 are laminated together to form a laminate S1 (second step). In one embodiment, in the second step, a plurality of green sheets 10 are sequentially laminated to form a laminate S1. The plurality of green sheets 10 may be laminated so that the first main surfaces 10a are in contact with each other, or so that the second main surfaces 10b are in contact with each other, or so that the first main surfaces 10a and the second main surfaces 10b are in contact with each other. In addition, the plurality of green sheets 10 may be laminated after removing the excess portions of each of them using a Thomson blade or the like. The laminate S1 is a laminate of a plurality of green sheets 10. Therefore, the interfaces between the plurality of green sheets 10 exist on the side surfaces of the laminate S1.
[0057] 3(b) shows an example in which two green sheets 10 are laminated together, but the number of green sheets 10 is not limited to this. The number of green sheets 10 may be two or more, and may be ten or less, eight or less, six or less, or four or less. The thickness of the laminate S1 is, for example, 800 μm or more and 4000 μm or less.
[0058] In the second step, an organic solvent may be applied to the surface of at least one of the plurality of green sheets 10, and then the plurality of green sheets 10 may be laminated together. For example, an organic solvent may be applied to one main surface of one green sheet 10, and then another green sheet 10 is laminated on the same surface.
[0059] The organic solvent may be, for example, any of the above-mentioned solvents other than water. The organic solvent may be one or more selected from the group consisting of carbon tetrachloride, chloroform, tetrahydrofuran, toluene, butyl acetate, methyl acetate, ethyl acetate, ethanol, n-butanol, and acetone.
[0060] (Crimping) After the second step, the laminate S1 is pressed (third step). In one embodiment, in the third step, the laminate S1 is pressed in the stacking direction of the green sheet 10 (the direction of the arrow in FIG. 3(b)) to press the laminate S1. For example, a batch press machine, a continuous roll press machine, or the like can be used to press the laminate S1. The use of a continuous roll press machine can further increase productivity. In the third step, the laminate S1 is pressed with a pressure of, for example, 130 kPa or more and 1380 kPa or less. The pressure may be 180 kPa or more, 230 kPa or more, or 270 kPa or more. In addition, the pressure may be 1200 kPa or less, 1000 kPa or less, 800 kPa or less, or 650 kPa or less from the viewpoint of suppressing dimensional distortion of the obtained lithium ion conductive sheet 1.
[0061] The pressurization is performed for, for example, 1 second to 60 minutes. The pressurization time may be 5 seconds or more, and may be 50 minutes or less, 40 minutes or less, 30 minutes or less, or 20 minutes or less.
[0062] In the third step, heating may be performed together with the pressing. In the third step, the laminate S1 is pressed under conditions of, for example, 30° C. or higher and 200° C. or lower. The temperature may be 50° C. or higher, or 70° C. or higher, and may be 180° C. or lower, 150° C. or lower, or 130° C. or lower.
[0063] The heating time may be the same as the pressurizing time, and the heating is performed for, for example, 1 second to 60 minutes.
[0064] The third step provides a laminate S2 that is bonded to the pressure. As described above, the laminate S1 has an interface between the green sheets 10 on the side surface. The interface may disappear due to the pressure and / or heat applied in the third step. That is, the interface between the green sheets 10 may disappear by the end of the third step. In other words, the interface and grooves resulting from the interface may not be provided on the side surface of the laminate S2 that is bonded to the pressure. The thickness of the laminate S2 that is bonded to the pressure is, for example, 800 μm or more and 4000 μm or less.
[0065] (Firing) After the third step, the compressed laminate S2 is fired (fourth step). As shown in Fig. 3(c) in one embodiment, in the fourth step, the compressed laminate S2 is placed on a placement surface 50a of a setter 50.
[0066] The setter 50 is a heat-resistant member that supports the laminate S2 that has been pressed, and is made of, for example, aluminum oxide (alumina), titanium oxide, silicon oxide (silica), zirconium oxide, yttrium oxide, or a composite oxide thereof. From the viewpoints of cost and durability, the setter 50 may be an alumina-based setter that contains alumina. In this case, the purity of the alumina in the setter 50 is, for example, 99% or more. The porosity of the setter 50 is, for example, 50% or less. From the viewpoint of making it easier to peel off the lithium ion conductive sheet 1 from the setter 50, at least a part of the mounting surface 50a of the setter 50 may have an oxide containing at least one of lanthanum, titanium, and lithium. The oxide is, for example, lanthanum oxide, titanium oxide, lithium oxide, lanthanum-titanium oxide, lanthanum-lithium oxide, titanium-lithium oxide, or lanthanum-titanium-lithium oxide. When the setter 50 is an alumina setter, the oxide is formed by baking a powder containing at least one of a lanthanum raw material, a titanium raw material, and a lithium raw material onto the mounting surface 50a of the setter 50. Specifically, the setter 50 on which the powder is placed on the mounting surface 50a is heated, so that the powder becomes part of the mounting surface 50a. The powder is placed on the mounting surface 50a by using, for example, a sieve, a brush, or the like.
[0067] Next, the laminate S2 on the setter 50 is degreased. For example, the laminate S2 is degreased in a process of increasing the temperature from room temperature to 500°C over 54 hours. Next, the degreased laminate S2 is fired to produce the lithium ion conductive sheet 1. For example, the laminate S2 is fired at 1100°C to 1500°C using a known method such as an electric furnace different from the device used in the degreasing. Here, firing in an electric furnace corresponds to holding the electric furnace in which the laminate S2 is fired at a predetermined temperature for a predetermined time. The laminate S2 is fired for 10 minutes to 6 hours, for example, in an air atmosphere or a low oxygen concentration atmosphere. This removes organic components such as binders and solvents, and a composite oxide sheet (lithium ion conductive sheet) composed of oxides containing lanthanum, lithium, and titanium is formed.
[0068] Next, the effect of the lithium ion conductive sheet 1 manufactured by the manufacturing method according to this embodiment will be described in comparison with the manufacturing method according to the reference example described below. In the manufacturing method according to the reference example, a lithium ion conductive sheet is obtained by firing one green sheet in the same manner as in this embodiment. Here, it is considered to enlarge the area of the main surface of the lithium ion conductive sheet for the purpose of increasing the amount of liquid that can be processed per sheet and improving the lithium recovery efficiency. However, simply enlarging the area makes the lithium ion conductive sheet more likely to break. That is, simply enlarging the area makes the durability of the lithium ion conductive sheet more likely to decrease. From the viewpoint of suppressing the decrease in durability of the lithium ion conductive sheet, thickening of the sheet is considered. When the area is enlarged and the thickness is increased (i.e., the size is increased) by the manufacturing method according to the reference example as described above, the thickness of the lithium ion conductive sheet manufactured becomes significantly uneven. For this reason, in the above reference example, even when the thickness is increased due to the area enlargement, the lithium ion conductive sheet is easily broken in the thin parts, and sufficient durability tends not to be obtained.
[0069] In contrast, in the manufacturing method according to the present embodiment, first, a plurality of thin green sheets 10 are formed, and the plurality of green sheets 10 are stacked on one another and pressed to form a thick pressed laminate S2. Then, the pressed laminate S2 is fired to obtain a lithium ion conductive sheet 1. Here, the green sheet 10 has a reduced thickness variation compared to a thickened green sheet. Therefore, the thickness variation of the laminate S2, which is made large by stacking a plurality of green sheets 10, is also reduced compared to a simply thickened green sheet. Then, the pressed laminate S2 is fired to produce a lithium ion conductive sheet 1 with reduced thickness variation. Thus, according to the manufacturing method according to the present embodiment, even when a large lithium ion conductive sheet 1 is manufactured, the thickness variation can be reduced. Therefore, a lithium ion conductive sheet 1 that is less likely to break even when it is large, that is, has excellent durability, can be manufactured.
[0070] The above embodiment describes one aspect of the present invention. Therefore, the present invention may be modified without being limited to the above embodiment. For example, in the above embodiment, the excess part is removed before peeling off the green sheet 10, which is a dried slurry, but the present invention is not limited to this. The slurry may be applied in a form placed on one side of the base film. In this case, the green sheet 10 can be formed without removing the excess part. EXAMPLES
[0071] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples.
[0072] (slurry) As raw material powders, lanthanum oxide (manufactured by Kanto Chemical Co., Ltd.), anatase-type titanium oxide (manufactured by Teika Co., Ltd.), and lithium carbonate (manufactured by Kishida Chemical Co., Ltd.) were prepared. Lanthanum oxide was used after being placed in an alumina sagger, and then heated and dried at 700°C for 1 hour. Then, a total of 100 parts by mass of mixed powder consisting of 50.4 parts by mass of lanthanum oxide, 43.6 parts by mass of titanium oxide, and 6.0 parts by mass of lithium carbonate was placed in a nylon mill loaded with zirconia balls. Here, not only the mixed powder but also 103.4 parts by mass of a mixed liquid of a dispersant and a solvent was placed in the nylon mill. In the mixed liquid, the dispersant was a commercially available polycarboxylate-type polymer dispersant of 3.7 parts by mass, and the solvent was a mixed solvent of toluene and ethyl acetate (solvent toluene mass: ethyl acetate mass = 3:2). Then, the mixed powder and the mixed liquid were milled for 20 hours. Next, a binder made of a methacrylate copolymer (manufactured by Nippon Shokubai Co., Ltd., number average molecular weight: 37,000, glass transition temperature: 19°C) and a plasticizer (dibutyl phthalate) were added to the nylon mill. Here, 28.4 parts by mass of the binder and 19.2 parts by mass of the plasticizer were added in terms of solid content. Next, a slurry was prepared by further milling for 20 hours.
[0073] Next, the prepared slurry was transferred to a jacketed round-bottom cylindrical vacuum degassing vessel equipped with an anchor-shaped stirrer. The slurry was then concentrated and degassed under reduced pressure and a jacket temperature of 40°C while rotating the stirrer at 200 rpm. This resulted in a slurry (Slurry A) with a viscosity adjusted to 3 Pa s at 25°C. Additionally, a slurry (Slurry B) with a viscosity adjusted to 3 Pa s at 25°C was obtained in the same manner as Slurry A, except that the blending ratio of each component was changed.
[0074] The content of each component in the slurry A and slurry B after viscosity adjustment is shown in Table 1. The content of each component means the content based on the total amount of solids in the slurry A or B.
[0075] [Table 1]
[0076] <Example 1> (Green Sheet) Using a coating device, the slurry A was continuously coated onto the PET film, which was a base film. At this time, the slurry A was coated by the doctor blade method. Next, in the same coating device, the coated slurry A was dried at 100°C for 2 hours. As a result, a sheet (green sheet) with a thickness of about 800 μm and a long length in plan view was obtained. This green sheet was peeled off from the base film. Hereinafter, the surface included in the green sheet and in contact with the PET film, which was a base film, is referred to as the "PET surface." In addition, the surface included in the green sheet and opposite to the PET surface in the thickness direction of the sheet may be referred to as the "Air surface."
[0077] (Laminate) Two green sheets were prepared by the above method and peeled off from the base film, and each green sheet was cut into an 18 cm square. The two cut green sheets were laminated in the thickness direction so that the air surfaces of the two cut green sheets were in contact with each other to form a laminate. The laminate was pressed by a press machine at a pressure of 308 kPa while heating at a temperature of 100°C for 1 minute, thereby bonding the laminate. The laminate was then punched out with a Thomson blade to obtain a bonded laminate (15 cm square) that had a rectangular shape in plan view.
[0078] (Setter) First, the same mixed powder as the raw material powder used in the production of the green sheet was prepared. The mixed powder was then placed in a nylon mill loaded with zirconia balls. A mixed powder was then obtained by dry mixing for 20 hours. The mixed powder was then placed in an alumina sagger, and the sagger was then placed in a high-temperature box-type electric furnace. The electric furnace was then heated to 1350°C and held for 2 hours. This resulted in the mixed powder in the sagger being calcined. The calcined mixed powder was pulverized in a mortar and then sieved through a wire mesh with an opening of 500 μm. The powder that passed through the wire mesh was then collected.
[0079] Next, the powder sifted through the wire mesh was placed on the mounting surface of an alumina setter (manufactured by Yotai Co., Ltd., alumina about 99%, porosity: 16.9%, bulk density 3.2). At this time, the powder was spread thinly and uniformly on the mounting surface using a brush. Next, the setter on which the powder was spread was placed was placed in a high-temperature box-type electric furnace, and the electric furnace was heated to 1350°C and held for 2 hours. As a result, the mixed powder, which was the same as the raw material powder, was baked onto the mounting surface of the setter. After the setter was cooled, the entire amount of the powder was baked. In other words, after the setter was cooled, no falling off of the powder was observed.
[0080] (Lithium ion conductive sheet) The laminated body produced by the above method was placed on the mounting surface of the setter. Next, the setter and the laminated body on the setter were placed in an electric furnace, and the laminated body was degreased by heating the electric furnace from room temperature to 500°C over 54 hours. Next, the setter and the degreased laminated body on the setter were placed in a high-temperature box-type electric furnace, and the laminated body was fired by heating the electric furnace to 1350°C and holding it for 1 hour. As a result, a composite oxide sheet (lithium ion conductive sheet) having a perovskite-type crystal structure composed of oxides containing Li, La, and Ti as constituent elements was obtained.
[0081] <Examples 2 to 6> In producing the laminate, the lithium ion conductive sheets of Examples 2 to 6 were obtained in the same manner as in Example 1, except that the type of slurry, the pressure applied when pressing the laminated green sheets, and the heating time were changed as shown in Table 2.
[0082] <Comparative Example 1> Using a coating device, the slurry B was continuously coated onto a PET film, which was a base film. At this time, the slurry was coated by a doctor blade method. Next, in the same coating device, the coated slurry was dried at 100°C for 6.5 hours. As a result, a sheet (green sheet) with a thickness of about 1.6 mm and a long length in plan view was obtained. After peeling off the green sheet from the base film, it was punched out with a Thomson blade to obtain a green sheet (15 cm square) with a rectangular shape in plan view.
[0083] A lithium ion conductive sheet of Comparative Example 1 was obtained in the same manner as described in "(Lithium ion conductive sheet)" of Example 1 above, except that the "green sheet" obtained by the above method was used instead of the "laminate".
[0084] <Comparative Example 2> A lithium ion conductive sheet of Comparative Example 2 was obtained in the same manner as in Comparative Example 1, except that the slurry A was used instead of the slurry B.
[0085] [evaluation] For the lithium ion conductive sheets of Examples 1 to 6 and Comparative Examples 1 and 2, the thickness and its variation coefficient, the area of the main surface, the porosity, and the dimensional distortion were evaluated by the following methods.
[0086] (Measurement of thickness and coefficient of variation of thickness) The thickness of each of the lithium ion conductive sheets of Examples 1 to 6 and Comparative Examples 1 and 2 was measured at nine arbitrary points using a micrometer. Here, the nine arbitrary points for measuring the thickness were points located at the approximate center (centroid) of each section when the main surface of each lithium ion conductive sheet was divided into three sections in the vertical and horizontal directions, resulting in nine sections having approximately the same area. Based on the measurement results, the arithmetic mean was calculated as the "thickness". In addition, the standard deviation was calculated based on the measurement results, and the "coefficient of variation of thickness" was calculated by the following formula. "Coefficient of variation of thickness" = standard deviation / "thickness"
[0087] (Measurement of the area and porosity of the main surface of the lithium ion conductive sheet) For each of the lithium ion conductive sheets of Examples 1 to 6 and Comparative Examples 1 to 2, the main surface of the lithium ion conductive sheet was photographed from a direction perpendicular to the main surface with a digital camera (manufactured by Olympus Corporation, "Tough TG-6") to obtain an image of the main surface. The photographing was performed while applying light from the back of the lithium ion conductive sheet. An image of the main surface of the lithium ion conductive sheet manufactured in Example 3 is shown in FIG. 4. In the main surface image of the lithium ion conductive sheet, the part where voids exist and the part where voids do not exist have clearly different brightness (color depth) when illuminated from the back with a light source, so that the two can be clearly distinguished from each other. In the example shown in FIG. 4, for example, the dark color part existing inside the ellipse in FIG. 4 corresponds to the void part. Next, the obtained image of the main surface was analyzed by image analysis software (manufactured by Hakuto Co., Ltd. System Products Company, "Image pro plus") to obtain the area of the main surface of each lithium ion conductive sheet and the area of the void part observed on the main surface. More specifically, the obtained image was binarized to divide the image into the main surface of the lithium ion conductive sheet and the other (background) portions, and the area of the main surface of the lithium ion conductive sheet (area of the main surface) was obtained. Next, the main surface of the lithium ion conductive sheet was binarized to divide the image into portions where voids exist (portions with dark colors) and portions where voids do not exist (portions with light colors), and the area of the portions where voids exist (area of the void portions) was obtained. Next, the porosity was calculated by the following formula. Porosity [%] = (area of voids [cm 2 ] / area of main surface [cm 2 ])×100
[0088] (Dimensional distortion) The lithium ion conductive sheets of Examples 1 to 6 and Comparative Examples 1 to 2 were evaluated for the presence or absence of dimensional distortion. First, the distance between one side M1 of the four sides constituting the main surface of the lithium ion conductive sheet and the side M2 opposite to the side M1 was measured from the image of the main surface using a vernier caliper (manufactured by Mitutoyo Corporation, model number: CD-15 (500-301)). At this time, the distance was measured at five equally spaced points from one end to the other end of the side M1. In addition, the distance between a pair of sides N1 and N2 different from the sides M1 and M2 was similarly measured at five points. The standard deviation was calculated for the five measured values obtained for the distance between the sides M1 and M2 and the distance between the sides N1 and N2. If any of the standard deviations was 0.4 or more, the dimensional distortion was determined to be "present". If any of the standard deviations was less than 0.4, the dimensional distortion was determined to be "absent".
[0089] [Table 2] [Explanation of symbols]
[0090] 1...lithium ion conductive sheet, 1a, 10a...first main surface, 1b, 10b...second main surface, 10...green sheet, 50...setter, 50a...mounting surface, S1...laminated body, S2...press-bonded laminate.
Claims
1. A first step of forming a plurality of green sheets by drying a coating of a slurry containing a lithium raw material, a lanthanum raw material, and a titanium raw material; a second step of laminating the plurality of green sheets together to form a laminate; A third step of pressing the laminate; A fourth step of firing the pressed laminate.
2. The slurry further comprises a binder, a plasticizer, a dispersant, and a solvent; The content of the binder is 10.0% by mass or more and 40.0% by mass or less based on the total amount of solids in the slurry, The content of the plasticizer is 1.0% by mass or more and 20.0% by mass or less based on the total amount of solids in the slurry, The method for producing a lithium ion conductive sheet according to claim 1 , wherein the content of the dispersant is 1.0 mass % or more and 5.0 mass % or less based on the total amount of solids in the slurry.
3. 3. The method for producing a lithium ion conductive sheet according to claim 1, wherein in the third step, the laminate is pressed at a pressure of 130 kPa or more and 1,380 kPa or less under a condition of 30° C. or more and 200° C. or less to bond the laminate.
4. 3. The method for producing a lithium ion conductive sheet according to claim 1, wherein in the second step, an organic solvent is applied to a surface of at least one of the plurality of green sheets, and then the plurality of green sheets are laminated together.
5. 3 . The method for producing a lithium ion conductive sheet according to claim 1 , wherein interfaces between the green sheets present on the side surfaces of the laminate in the second step disappear by the time the third step is completed. 4 .
Citation Information
Patent Citations
Method for producing lithium separation sheet
JP2021160945A